2019
DOI: 10.1557/jmr.2019.166
|View full text |Cite
|
Sign up to set email alerts
|

Effects of biomimetic micropattern on titanium deposited with PDA/Cu and nitric oxide release on behaviors of ECs

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Furthermore, HR tests revealed that LDH/PDA/Hep coating had a low HR (0.65%) in vitro, implying that heparinization was a promising strategy to enhance the hemocompatibility of samples. Li et al [ 242 ] conjugated the Hep molecule, the Arg–Glu–Asp–Val peptide (REDV, which is a tetrapeptide derived from fibronectin that can be specifically recognized by α 4 β 1 integrin on the surface of ECs [ 243 ]), and an anti-CD 34 antibody (CD 34 is a highly glycosylated type I transmembrane glycoprotein that interacts with anti-CD 34 antibodies and is an important way to promote EPC-targeted adhesion/capture [ 244 , 245 ]) on a silane-treated ZE21B alloy, for improving surface endothelialization. A blood compatibility test suggested that multi-functional coating effectively restrained platelet adhesion/activation and reduced the HR (<5%).…”
Section: Surface Modification Of Mg Alloy Stentsmentioning
confidence: 99%
“…Furthermore, HR tests revealed that LDH/PDA/Hep coating had a low HR (0.65%) in vitro, implying that heparinization was a promising strategy to enhance the hemocompatibility of samples. Li et al [ 242 ] conjugated the Hep molecule, the Arg–Glu–Asp–Val peptide (REDV, which is a tetrapeptide derived from fibronectin that can be specifically recognized by α 4 β 1 integrin on the surface of ECs [ 243 ]), and an anti-CD 34 antibody (CD 34 is a highly glycosylated type I transmembrane glycoprotein that interacts with anti-CD 34 antibodies and is an important way to promote EPC-targeted adhesion/capture [ 244 , 245 ]) on a silane-treated ZE21B alloy, for improving surface endothelialization. A blood compatibility test suggested that multi-functional coating effectively restrained platelet adhesion/activation and reduced the HR (<5%).…”
Section: Surface Modification Of Mg Alloy Stentsmentioning
confidence: 99%
“…Fibronectin coating can enhance migration of some cell types but not of some other types . Heparin, which is used to develop heparinized surfaces, can promote migration of endothelial cells (ECs) but inhibit that of smooth muscle cells (SMCs). , Some peptides like REDV (Arg–Glu–Asp–Val) have been reported to selectively promote endothelial cell layer formation on stent surfaces rather than other cell types. , Nitric oxide (NO) donors, which can be immobilized on micropatterned surfaces to provide biological signal molecules, can inhibit migration of SMCs but enhance migration of ECs . Nevertheless, available tools to adjust cell migration are still very limited.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Nitric oxide (NO) donors, which can be immobilized on micropatterned surfaces to provide biological signal molecules, can inhibit migration of SMCs but enhance migration of ECs. 13 Nevertheless, available tools to adjust cell migration are still very limited. What's more, the reported ways can only regulate the relative migration speed in a unidirectional manner, namely, either enlarged or reduced via one tool.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, TNT‐P12Cu3 showed negligible changes compared with TNT‐P12 from FTIR spectrum in Figure 2b, revealing PDA films successfully deposited on TNT surfaces. The absorption peak of 1680 cm −1 is attributed to the stretching vibrational peak of C=O in the amide bond, while the multiple consecutive absorption peaks in the 1640 cm −1 ‐1540 cm −1 range belong to the benzene ring skeleton vibrational peaks [32].…”
Section: Resultsmentioning
confidence: 99%